Elaboration of new model for predicting early clinical deterioration in patients with acute spontaneous supratentorial intracerebral hemorrhage and secondary intraventricular hemorrhage - Kuznietsov, A. A.; Kozyolkin, O.; Кузнєцов, Антон Анатолійович; Козьолкін, Олександр Анатолійович (John Wiley & Sons, Ltd., 2017)
Background and aims: Predicting early clinical deterioration (ECD) in patients with acute spontaneous supratentorial intracerebral hemorrhage (ASSICH) and secondary intraventricular hemorrhage (IVH) is a very important and relevant in modern angioneurology, that can help the practicioners choose optimal treatment approaches to improve its efficacy. The aim was elaboration new statistical model forBackground and aims: Predicting early clinical deterioration (ECD) in patients with acute spontaneous supratentorial intracerebral hemorrhage (ASSICH) and secondary intraventricular hemorrhage (IVH) is a very important and relevant in modern angioneurology, that can help the practicioners choose optimal treatment approaches to improve its efficacy. The aim was elaboration new statistical model for predicting early clinical deterioration (ECD) in patients with ASSICH and secondary IVH. predicting early clinical deterioration (ECD) in patients with ASSICH and secondary IVH.